An evaluation of the effectiveness of Iloilo City government in regulating solid waste disposal on selected Barangays in Iloilo City Proper. - Jallorina, Stephanie L.; Nerpiol, Rona N. (2004.)
This study is an evaluation on how effective is the Iloilo City government in regulating solid waste disposal in Barangays Danao and Flores of the Iloilo City Proper. A survey was conducted among the 25 households and 27 commercial establishments of Barangay Danao and among the 33 households and 27 commercial establishments of Barangay Flores. Personal interviews with the heads of the Office of Public Services, Department of Environment and Natural Resources-Environmental Management Bureau, Department of Health-Environmental Sanitation Inspection, City Environment and Natural Resources Office and J.S. Layson & Co. Inc. wee conducted to solicit substantial information about the regulation and regulatory mechanisms. Secondary data and library materials were also utilized as references for the casual study. The study utilizes the Likert-type scale as a statistical tool for the survey results., Based on findings, collection of fees is the only mechanism employed by the city to regulate solid waste disposal. The respondents of two barangays do not have a sense of responsibility towards their garbage at the pre-collection stage. It was found out that solid waste management programs are poorly implemented, thus, people do not segregate and recycle their garbage. Moreover, no legislation has been pursued for a decade and even under the current administration. The city adopts antiquated ordinances and national environmental laws. The city government is rated "more effective" because of limited logistics and budget. Despite the local initiatives and coordination of the regulatory institutions, solid waste problem is still an issue in the city.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Solid Waste Disposal